(untitled) (Palíndromo, 2022)
For a dossier with the theme of “Details”, we will focus on details in works that deal with the figure of Saint Jerome, creating a visual narrative of the saint’s life. The detail in the work, works in detail, the visual detail as a plastic element, with its minutiae, iconography and possible interpretation. What possible subliminal messages permeate the details, objects, scenery, elements that accompany the fascinating figure of this saint so observed by artists from such different times? What can this figure tell us even today? Based on authors who deal with the theme of details, from the images of Saint Jeronimo that appear in the Mnemosyne Atlas, it also discusses the identity of a reader and the possible interpretations of a work.